Randomised placebo controlled trial of nebulised corticosteroids in acute respiratory syncytial viral bronchiolitis. Issue 2 (1st February 2000) - Cade, A; Brownlee, K G; Conway, S P; Haigh, D; Short, A; Brown, J; Dassu, D; Mason, S A; Phillips, A; Eglin, R; Graham, M; Chetcuti, A; et al.
Abstract : OBJECTIVE: To evaluate short and long term effects of giving nebulised budesonide early in respiratory syncytial viral (RSV) bronchiolitis. DESIGN: A multicentre randomised double blind placebo controlled trial. SUBJECTS: Infants admitted to hospital with their first episode of RSV positive bronchiolitis. INTERVENTION: Randomisation to receive either 1 mg of nebulised budesonide (Bud) or placebo (Pla) twice daily from admission until 2 weeks after discharge. Follow up was for 12 months. MAIN OUTCOME MEASURES: Duration of hospital admission, time taken to become symptom free, re-admission rates, general practitioner consultation rates, and use of antiwheeze medication during follow up. RESULTS: 161 infants were studied. Both arms were similar with respect to initial clinical severity, age, sex, socioeconomic class, and tobacco exposure. Median time from first nebulisation to discharge: Bud and Pla, 2 days. Median number of days for 50% of infants to be symptom free for 48 hours: Bud, 10 days; Pla, 12 days. Respiratory re-admission rates in the 12 month follow up: Bud, 16%; Pla, 18%; median difference (95% confidence interval (CI)), −2 (−14 to 10). Median respiratory related general practitioner attendances: Bud, 4.0; Pla, 4.5; median difference (95% CI), −1 (−2 to 0). Percentage of infants receiving at least one prescription for antiwheeze medication during follow up, corticosteroids: Bud, 50%; Pla, 60%; difference (95% CI), −10 (−26 to 6); bronchodilators: Bud, 60%; Pla, 67%; difference (95% CI), −7 (−22 to 8). CONCLUSIONS: There are no short or long term clinical benefits from the administration of nebulised corticosteroids in the acute phase of RSV bronchiolitis.